Quranic motivation toward modern approach for e-Da'wah - Eddine, Meftah Mohammed Charaf; Zeki, Akram M. (Centre of Quranic Research, University Malaya, 2019)
The world today need to know Islam correctly. In our days there are more than five billion people who do not believe in Islam all over the world.